Variable model for mechanical parameters of soft rock and elastoplastic solutions for tunnels considering the influence of confining pressure - Dong, Yucang; Zhang, Hai; Wang, Mingnian; Yu, Li; Zhu, Yongquan (Frontiers in Earth Science, 2023)
The accurate understanding of the influence of confining pressure on the mechanical characteristics of soft rock and how to comprehensively consider this influence in the elastoplastic analysis of tunnels are the fundamental premises for the effective evaluation of the deformation control and stability of soft rock tunnels. Therefore, this paper firstly investigates the effect of confining pressure on the deformation and strength characteristics of phyllite and slate, using triaxial experiment results and proposed variable models for the mechanical parameters (E, v, c, φ) of soft rock with confining pressure variation. Secondly, according to the second stress state around tunnels and these variable models for the mechanical parameters of soft rock, a new elastoplastic solution for tunnels is devised, which simultaneously considers the effect of confining pressure on the deformation and strength characteristics of the surrounding rock. Finally, with the proposed elastoplastic solution, the effect of multiple factors (initial pressure, supporting force, and tunnel radius) on the stress and displacement of tunnel surrounding rock is analyzed.